Answer:
The table:
y = x y = 2/3 x y = 2/3 x + 1
-6 → -4 → -3
-3 → -2 → -1
0 → 0 → 1
3 → 2 → 3
6 → 4 → 5
Explanation:
- We have three equations:
1. y = x
2. y =
x
3. y =
x + 1
∵ Equation 2 =
× equation 1
- That means we multiply the value of y by
![(2)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jgft8n5xwx5uidfnxss9gbutm3s8nfmtko.png)
∵
< 1
∴ Equation 2 is the image of equation 1 by vertical compression with
scale factor
![(2)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jgft8n5xwx5uidfnxss9gbutm3s8nfmtko.png)
∵ Equation 3 = equation 2 + 1
- That means we add the value of y by 1
∴ Equation 3 is the image of equation 2 by translation 1 unit up
- To fill the table we will multiply each y value by
to
find the values of the equation 2 and then add 1 to find the values of
equation 3
→ The 1st equation y = x
∵ x = -6 , -3 , 0 , 3 , 6
∴ y = -6 , -3 , 0 , 3 , 6
→ The 2nd equation y =
x
∵ x = -6 , -3 , 0 , 3 , 6
∴ y = -4 , -2 , 0 , 2 , 4
→ The 3rd equation y =
x + 1
∵ x = -6 , -3 , 0 , 3 , 6
∴ y = -3 , -1 , 1 , 3 , 5
The table:
x → y = x → y = 2/3 x → y = 2/3 x + 1
-6 → -6 → -4 → -3
-3 → -3 → -2 → -1
0 → 0 → 0 → 1
3 → 3 → 2 → 3
6 → 6 → 4 → 5